Developing a Nigerianspecific food and nutrient coding database - Day, R.S.; Douglass, D.L.; Maziya-Dixon, B.B. (2008)
A Nigerian-specific food and nutrient coding database was developed by adding Nigerian-specific foods, recipes, measure descriptions, and gram weights to information from the US Department of Agriculture (USDA) databases used for the 1994–1996, 1998 Continuing Survey of Food Intakes by Individuals. The Nigerian database was used to analyze intakes from the 2001 Nigerian Food Consumption and Nutrition Survey. The Food Intake Analysis System (FIAS) (developed by The University of Texas School of Public Health and the USDA Agricultural Research Services Food Surveys Research Group) and food and nutrient data from the USDA databases were used to aid creation of foods and recipes specific to Nigeria. USDA data had only 214 of the basic foods reported consumed by Nigerians. Researchers developed food descriptions and nutrient profiles for another 117 foods specific to Nigerian intake. An additional 14 foods were created from ingredients in the USDA database. Complete profiles of 14 nutrients were included for every new food from food composition books and tables. A total of 422 recipes were created from the USDA and Nigerian foods using the nutrient retention factor recipe methodology and the FIAS software. Recipes were kitchen tested to obtain a weight before and after cooking, and the weight of a typical serving. It was necessary to add measure descriptions and gram weights to 359 USDA and 164 Nigerian foods. Development of this unique population-specific database of foods and recipes for this African country constitutes an important milestone for future diet and nutrition studies.